Valproic Acid and Thrombocytopenia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The association of thrombocytopenia (TCP) with valproic acid (VPA) therapy was evaluated retrospectively in 167 children treated with VPA between 1989 and 1993 at the Department of Pediatrics, Henry Ford Medical Center, Detroit, MI.